2015
DOI: 10.14359/51687129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Slag Cement on Drying Shrinkage of Concrete

Abstract: The effect of a partial replacement of cement with slag cement on free shrinkage is evaluated for curing periods between 3 and 28 days. Mixtures include concrete containing different replacement levels of slag cement (30, 60, and 80% by volume)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 3 publications
(2 reference statements)
2
15
0
Order By: Relevance
“…They found that a partial replacement of cement with slag cement reduced shrinkage-a reduction that was greatest at early ages and increased as the replacement level of slag was increased. Yuan et al (2015) also found, as did Darwin et al (2007) and Lindquist et al (2008), that when slag cement was used in conjunction with a saturated porous limestone coarse aggregate, which provided internal curing, a greater reduction in shrinkage was observed than obtained in mixtures containing a low-absorption coarse aggregate.…”
Section: Effects Of Internal Curing Slag and Silica Fume On Concretmentioning
confidence: 62%
See 2 more Smart Citations
“…They found that a partial replacement of cement with slag cement reduced shrinkage-a reduction that was greatest at early ages and increased as the replacement level of slag was increased. Yuan et al (2015) also found, as did Darwin et al (2007) and Lindquist et al (2008), that when slag cement was used in conjunction with a saturated porous limestone coarse aggregate, which provided internal curing, a greater reduction in shrinkage was observed than obtained in mixtures containing a low-absorption coarse aggregate.…”
Section: Effects Of Internal Curing Slag and Silica Fume On Concretmentioning
confidence: 62%
“…The results indicate that: 1) internal curing using prewetted lightweight aggregate reduces the tendency of the mixtures to develop shrinkage strains at early ages; and 2) the reduction is significantly enhanced when internal curing is combined with slag cement or slag cement and silica fume. As observed by Darwin et al (2007), Lindquist et al (2008), and Yuan et al (2015), when a partial replacement of cement with slag cement is combined with internal curing provided by porous limestone coarse aggregate, there appears to be a synergistic effect when combining slag and silica fume with internal curing.…”
Section: Net Shrinkage Through 30 Daysmentioning
confidence: 70%
See 1 more Smart Citation
“…on the other hand, the capillary tension of concrete because of the water evaporation is increased with the pore size refinement of concrete, which leads to the increase of drying shrinkage. The development and change of drying shrinkage of concrete depend mainly on the proportions of the positive and negative effect of the pore size refinement [13][14][15][16]. Combined the results shown in Figure 3 with the results shown in Figure 4, the positive effect of pore size refinement on the drying shrinkage is greater than the negative effect.…”
Section: Pore Structurementioning
confidence: 92%
“…The study presented in this paper is part of a long-term research program at the University of Kansas to develop low-cracking high-performance concrete (LC-HPC) for bridge deck applications (Darwin et al 2004(Darwin et al , 2012Lindquist et al 2006Lindquist et al , 2008McLeod et al 2009McLeod et al , 2010Pendergrass and Darwin 2014;Yuan et al 2011Yuan et al , 2015.…”
Section: Introductionmentioning
confidence: 99%